Overexpression of AT2R in the solitary-vagal complex improves baroreflex in the spontaneously hypertensive rat - Ruchaya, Prashant J. [UNESP]; Speretta, Guilherme F. [UNESP]; Blanch, Graziela Torres [UNESP]; Li, Hongwei; Sumners, Colin; Menani, Jose V. [UNESP]; Colombari, Eduardo [UNESP]; Colombari, Debora S. A. [UNESP] (Churchill Livingstone, 2016)
The aim of this study was to investigate the physiological effects of increased angiotensin II type 2 receptor (AT2R) expression in the solitary-vagal complex (nucleus of the solitary tract/dorsal motor nucleus of the vagus; NTS/DVM) on baroreflex function in non-anaesthetised normotensive (NT) and spontaneously hypertensive rats (SHR). Ten week old NT Holtzman and SHR were microinjected with either an adeno-associated virus expressing AT2R (AAV2-CBA-AT2R) or enhanced green fluorescent protein (control; AAV2-CBA-eGFP) into the NTS/DVM. Baroreflex and telemetry recordings were performed on four experimental groups: 1) NTeGFP, 2) NTAT2R, 3) SHReGFP and 4) SHRAT2R (n = 4-7/group). Following in-vivo experimental procedures, brains were harvested for gene expression analysis. Impaired bradycardia in SHReGFP was restored in SHR rats over-expressing AT2R in the NTS/DMV. mRNA levels of angiotensin converting enzyme decreased and angiotensin converting enzyme 2 increased in the NTS/DMV of SHRAT2R compared to SHReGFP. Increased levels of pro inflammatory cytokine mRNA levels in the SHReGFP group also decreased in the SHRAT2R group. AT2R overexpression did not elicit any significant change in mean arterial pressure (MAP) in all groups from baseline to 4 weeks post viral transfection. Both SHReGFP and SHRAT2R showed a significant elevation in MAP compared to the NTeGFP and NTAT2R groups. Increased AT2R expression within the NTS/DMV of SHR was effective at improving baroreflex function but not MAP. We propose possible mediators involved in improving baroreflex are in the ANG II/ACE2 axis, suggesting a potential beneficial modulatory effect of AT2R overexpression in the NTS/DMV of neurogenic hypertensive rats. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Hypertension; ACE2; Baroreflex; Angiotensin II; Angiotensin receptor; NTS